2019
DOI: 10.1037/drm0000119
|View full text |Cite
|
Sign up to set email alerts
|

The neurocognitive theory of dreams at age 20: An assessment and a comparison with four other theories of dreaming.

Abstract: This article assesses the neurocognitive theory of dreams on the occasion of its 20th anniversary. The theory synthesizes findings from 3 strands of dream research, which focus respectively on the neural substrate that subserves dreaming, the development of dreaming in children, and quantitative findings on adult dream content, all 3 of which are necessary ingredients in any theory in cognitive neuroscience (Ochsner & Kosslyn, 2014). The article compares the current standing of the theory with that of 4 other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 206 publications
0
15
1
Order By: Relevance
“…The non-REM type dreams might occur on a daily basis (except on the days when their sleep is disturbed, Gravett et al, 2017), but the REM type dreams might occur only every third or fourth day when the elephants take the opportunity to lie down to sleep, indicating muscle atonia associated with REM sleep. This potentially irregular occurrence of REM sleep, and the absence of any clear form of REM sleep in cetaceans (see above), provide an important phylogenetic counter-argument to the hypothesized association between REM sleep and memory consolidation (Ackermann, Hartmann, Papassotiropoulos, de Quervain, & Rasch, 2014;Boyce, Glasgow, Williams, & Adamantidis, 2016;Humiston & Wamsley, 2018, 2019Magidov et al, 2018;Rasch, Pommer, Diekelmann, & Born, 2009;Siegel, 2001;Stickgold, 2005;Tilley & Empson, 1978;Wyatt, Fram, Kupfer, & Snyder, 1971).…”
Section: African Elephantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-REM type dreams might occur on a daily basis (except on the days when their sleep is disturbed, Gravett et al, 2017), but the REM type dreams might occur only every third or fourth day when the elephants take the opportunity to lie down to sleep, indicating muscle atonia associated with REM sleep. This potentially irregular occurrence of REM sleep, and the absence of any clear form of REM sleep in cetaceans (see above), provide an important phylogenetic counter-argument to the hypothesized association between REM sleep and memory consolidation (Ackermann, Hartmann, Papassotiropoulos, de Quervain, & Rasch, 2014;Boyce, Glasgow, Williams, & Adamantidis, 2016;Humiston & Wamsley, 2018, 2019Magidov et al, 2018;Rasch, Pommer, Diekelmann, & Born, 2009;Siegel, 2001;Stickgold, 2005;Tilley & Empson, 1978;Wyatt, Fram, Kupfer, & Snyder, 1971).…”
Section: African Elephantsmentioning
confidence: 99%
“…Typically, dreams are associated with REM sleep, these REM sleep dreams being the vivid, unfolding, narrative-type, mental representations recalled upon arousal (Aserinsky & Kleitman, 1953;Dement & Kleitman, 1957b;Jacobs, Feldman, & Bender, 1972;Leclair-Visonneau et al, 2010); however, subsequent studies have also shown that dreams occur during non-REM sleep (Foulkes, 1962;Hauri & van de Castle, 1973;Kales et al, 1967;McNamara et al, 2010;McNamara, McLaren, & Durso, 2007;Stickgold, Malia, Fosse, Propper, & Hobson, 2001;Suzuki et al, 2004). Indeed, it has been shown that non-REM sleep dream reports from late in the sleep period can be difficult to distinguish from REM sleep dream reports (Domhoff, 2017(Domhoff, , 2019Nir & Tonini, 2010;Siclari et al, 2018).…”
Section: Dreams In Humans and Eeg Statesmentioning
confidence: 99%
“…It is proposed to be a simulation of the waking world, of waking reality, or of waking consciousness. Thus, in general, dreaming can be defined as a simulated world (e.g., Revonsuo, 2000;Revonsuo et al, 2015;Domhoff, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…5 Yet finding a biological function for dreams themselves has evaded resolution. The ''null theory'' that dreams are byproducts of other adaptions, 6 or biological ''spandrels,'' 7 or sleep and dreams are adaptive only in that they prevent THE BIGGER PICTURE Dreaming remains a mystery to neuroscience. While various hypotheses of why brains evolved nightly dreaming have been put forward, many of these are contradicted by the sparse, hallucinatory, and narrative nature of dreams, a nature that seems to lack any particular function.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Yet finding a biological function for dreams themselves has evaded resolution. The ”null theory” that dreams are byproducts of other adaptions, 6 or biological ”spandrels,” 7 or sleep and dreams are adaptive only in that they prevent organisms from moving during periods that they are not adapted to, such as ensuring that diurnal animals are inactive during night, 8 , 9 are still taken seriously.…”
Section: Introductionmentioning
confidence: 99%